THE MEANING AND FUNCTION OF THE MANTRA PENGASIH REZEKI MARANG KUOSO IN THE PALAAN VILLAGE COMMUNITY - Fradam Hadi Suseno; Intan Subhana Permatasari; Riska Saputri (Journal of Indonesian Language Education and Literary, 2018)
Research on the meaning and function of the Mantra Pengasih Rezeki Marang Kuoso in Palaan village, Malang Regency that was carried out at launching sustenance through the God of SWT. The method used in this study is ethnography, with a type of qualitative research. The approach used is semiotic functional. The data source of this research is an informant from Palaan village, Malang Regency. This research data is in the form of interviews with the informant and observations made by researchers who show the meaning and function of Mantra Kuzor Marang Kuoso. The results of this study indicate that this mantra has different meanings and functions according to their purpose, and their inheritance must be through purification so that the recipient of the mantra is clean physically and spiritually. The function of this mantra is a companion to sustenance which is supported by two conditions namely religious conditions and material functions.